Novel In Vitro Screening System Based on Differential Scanning Fluorimetry to Search for Small Molecules against the Disassembly or Assembly of HIV-1 Capsid Protein - Miyazaki, Yasuyuki; Doi, Naoya; Koma, Takaaki; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2017)
Varieties of in vitro systems have been used to study biochemical properties of human immunodeficiency virus Gag-capsid protein (HIV Gag-CA). Recently, we have comparatively characterized HIV-1 and HIV-2 Gag-CA proteins using such technology, and have demonstrated that the NaCl-initiated CA-polymerization in vitro and the stability of CA N-terminal domain (NTD) as judged by differential scanning fluorimetry (DSF) are inversely correlated. In this study, we found that ZnCl2 works as a competent initiator of the in vitro HIV-1 CA-polymerization at much lower concentrations than those of NaCl frequently used for the polymerization initiation. We also showed by DSF assays that ZnCl2 highly destabilize HIV-1 CA. Furthermore, PF74, a well-known inducer of premature HIV-1 uncoating in infected cells, was demonstrated to unusually promote the HIV-1 CA-disassembly in the presence of ZnCl2 as revealed by DSF assays. Taken together, we conclude that the DSF method may be useful as an efficient monitoring system to screen anti-HIV-1 CA molecules.